Diplomacija virov - instrument preteklosti ali prihodnosti - Mancevič, Denis (Družboslovne razprave, 2012)
A cyclical energy crisis (2006-2009) strongly affected the long-lasting existing energy relations between the Russian Federation and the EU. The EU generally perceives the Federation's energy diplomacy as a negative tool of its external foreign policy. According to this perception, the main objectives of Russian energy diplomacy are primarily (geo)political, with a special emphasis on a "divide-et-impera" policy (so-called "energy imperialism"). In this article we attempt to look beyond this dominant scientific and political discourse and further develop alternative approaches (for example the "mutual interdependence" approach) to analyse the main characteristics of the formation and implementation of Russian energy diplomacy. This article develops the view that Russian energy diplomacy must be understood multidimensionally (beyond the dominant (neo)realist approaches), particularly with regard to the role and importance of Russian energy multinational companies in the process of formulating Russian foreign (energy) policies. The central objectives of Russian energy diplomacy in relation to the EU are not (geo)political, but economic.
Keywords: Diplomacija; Diplomacy; Foreign policy; Zunanja politika; Energetska politika; Energy policy; International business enterprises; Mednarodna podjetja; Rusija (Federacija); Russia (Federation); Države Evropske unije; European Union countries; Evropska unija; European Union